Factors of Export Diversification: Empirical Analysis of Russian Industrial Regions - Vasilyeva, Rogneda I.; Mariev, Oleg S.; Valentin A.; Urazbaeva, Alina R. (Economy of Regions, 2022)
Oil and gas dependence and the volatility of their prices is currently a serious challenge for the Russian economy. Coincidently, export revenues from oil and gas products are the main source of the federal budget. Export diversification can contribute to risk reduction for the Russian economy by increasing the share of products from other industries in the export structure. In this regard, the present study examines the determinants of export diversification in Russian industrial regions using econometric modelling methods. To this end, the Herfindahl and Theil indices for 97 export groups were calculated. It is hypothesised that the development of small and medium-sized enterprises, as well as the sanctions imposed by Western states against Russia are the main factors of export diversification in industrial regions. Simultaneously, natural resource extraction is assumed to significantly increase the concentration of exports in the regions. To test this hypothesis, panel data of 50 Russian industrial regions for the period 2001-2019 were analysed. The quantile regression approach was applied to solve the heteroscedasticity problem. Three groups of regions were distinguished according to their level of diversification: regions with a high level of export diversification (Q10-Q30), with an average level of diversification (Q40-Q60), with a low level of export diversification (Q70-Q90). The research findings show that the development of small and medium-sized enterprises contributes to export diversification in Russian industrial regions. While the sanctions did not have a significant impact on export diversification, regional potential and natural resource extraction increase the concentration of exports. The obtained study results complement the existing literature on export diversification in Russia, and contribute to the development of policy implications.